2010
DOI: 10.1586/epr.10.48
|View full text |Cite
|
Sign up to set email alerts
|

Salivary peptidomics

Abstract: In recent years, there has been an increased interest in the study of saliva. This bodily fluid contains a vast number of protein species, the salivary peptidome, of low molecular weight, comprising approximately 40-50% of the total secreted proteins, in addition to peptides generated by proteolysis of proteins of different sources. Owing to the presence of other components, in particular mucins and enzymes, some distinctive requirements and precautions related to sample collection, time of analysis, sample pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 153 publications
3
72
0
3
Order By: Relevance
“…This result reinforces the research in vivo and in situ studies by Amado et al (2010) showed statherin saliva made a major contribution in the formation of pellicle which would develop into plaque. Statherin produced by the parotid and submandibular glands.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result reinforces the research in vivo and in situ studies by Amado et al (2010) showed statherin saliva made a major contribution in the formation of pellicle which would develop into plaque. Statherin produced by the parotid and submandibular glands.…”
Section: Discussionsupporting
confidence: 89%
“…Biomarkers found in saliva potential as diagnostics can be identified if the composition of the protein in the pain compared to healthy individuals, it will describe the specific pathologic condition (Amado et al, 2010). Statherin a carbohydrate-free phosphoprotein very strong binding to the surface of the tooth enamel (Nakagaki et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Water is the main component of saliva (99%) buffered with electrolytes. A total of approximately 2,000 proteins constitute the salivary peptidome, of which approximately 400–600 are directly derived from salivary glands [3]. The salivary α-amylase represents the major enzyme secreted from the salivary glands [4].…”
Section: Introductionmentioning
confidence: 99%
“…It lubricates the oral cavity and participates in digestion and preventing infections (27 ). Saliva contains bacteria, cellular debris, crevicular fluid, and serum components, and as an alternative sample for noninvasive collection, saliva has promising, unique features (28 ). Proteolytic degradation occurs as soon as proteins enter the oral cavity and continues after a saliva sample is collected.…”
Section: Peptidomics Of Salivamentioning
confidence: 99%